Regulation of cellular steroid levels with special focus on oxysterol and estrogen metabolism. (June 2008) - Norlin, Maria
Steroids play essential roles in a number of physiological systems. However, disturbed functions or abnormal levels of steroids can result in serious health problems. The cellular levels of steroids are regulated by enzymes and other factors that control the formation and elimination of these compounds. Recent findings on steroid action and metabolism have identified novel links between two groups of steroids, oxysterols and estrogens. A better understanding of cellular processes related to these steroids is of interest for developing future therapies in several conditions, including endocrine tumors and hyperlipidemia.